2017
DOI: 10.22606/jaer.2017.23005
|View full text |Cite
|
Sign up to set email alerts
|

High School Student Rationales for Studying Advanced Science: Analysis of Their Psychological and Cultural Capitals

Abstract: Abstract. This study aimed to identify the psychological capitals (PsyCaps) and cultural capitals (CulCaps) of high school students who chose to study advanced science. Semi-structured interviews were conducted with 47 high school students in Taiwan to obtain the life experiences and rationales that motivated them to study science. Qualitative analysis of the science student data showed that PsyCaps and CulCaps tended to function in pairs and follow a PsyCap-CulCap configuration: interest (optimism)-materials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In particular, even without high SES or parental knowledge capital, children can still benefit from early numeracy activities in their later mathematics interest development. Confidence and interest are two major reasons for students to choose advanced science courses and careers (Chiu, 2017;Venville, Rennie, Hanbury, & Longnecker, 2013;Uitto, 2014). In this sense, early numeracy activities are a worthwhile investment, and the results of this study suggest that they be advocated by educators and policymakers and implemented by parents.…”
Section: Effects Of Early Numeracy Activities On Cognition and Affectmentioning
confidence: 75%
“…In particular, even without high SES or parental knowledge capital, children can still benefit from early numeracy activities in their later mathematics interest development. Confidence and interest are two major reasons for students to choose advanced science courses and careers (Chiu, 2017;Venville, Rennie, Hanbury, & Longnecker, 2013;Uitto, 2014). In this sense, early numeracy activities are a worthwhile investment, and the results of this study suggest that they be advocated by educators and policymakers and implemented by parents.…”
Section: Effects Of Early Numeracy Activities On Cognition and Affectmentioning
confidence: 75%
“…The research has indicated that extrinsic value or motivation is related to social norms and authorities in students' lives (Chiu, 2017). The affect experiences detected through online learning may be more likely to mediate or reflect students' inner-oriented motivations (e.g., self-concept and interest) than their extrinsic value.…”
Section: Valuementioning
confidence: 99%